Lyvia Morgan, KEOS XI. Wallpaintings and Social Context. The Northeast Bastion at Ayia Irini. - Dickinson, Oliver (Journal of Greek Archaeology, 2022)
Lyvia Morgan, KEOS XI. Wallpaintings and Social Context. The Northeast Bastion at Ayia Irini. pp. 533 + xxix, 74 plates, 102 figs, 2 tbls. Philadelphia: INSTAP Academic Press, 2020. ISBN 9781931534970, hardcover 80.